Limitações ao direito de greve do servidor público: uma análise a partir da teoria dos direitos fundamentais - Santos, Rosilene dos (2018)
The aim of this dissertation is to build a narrative about the right of public servants to strike. Current practices by the Legislative, Executive and Judiciary Branches, especially the most recent decisions of the Federal Supreme Court (STF), point to the need of an in-depth exploration of the inherent characteristics that involve the right of the public servants to strike, such as the basic core of this right, and how to find an appropriate basis that allows this right to be fully enjoyed based on the Theory of Horizontal Efficacy of Fundamental Rights. The public servants’ right to strike is very complex due to the relations that unfold as from the outbreak of the strike movement. The object of investigation of this dissertation regards the relations that occur in the horizontal line of fundamental rights, insofar as the exercise of this fundamental right is opposed to other equally basic rights. Decrees such as Federal Decree 7,777/2012 demonstrate how troublesome is the legislative omission that has lasted for more than 29 years since the Federal Constitution was promulgated. It is crucial to understand the strike as a mechanism for the defense of rights, as a social fact that, being very complex, requires parameters that allow full enjoyment when in conflict with other equally fundamental rights. It is essential that strike in the public service be understood as a right that needs special protection so that, when it conflicts with the fundamental rights of third parties, it is not considered a crime, as if the intention of the strike were to reach the public matter. The public servants’ strike is a fundamental right, and as such, must be respected and guaranteed in its full effectiveness.